Contextual analysis of the principles and procedures for making recourse against international arbitral award (2017)
An arbitral award once recognised by a court of competent jurisdiction, is on the same pedestal as the judgment of a court and therefore enforceable like court judgments. However, an award may be set aside on a good cause shown. The thrust of this paper is, therefore, to undertake contextual analysis of the principles and procedures for making recourse against arbitral award. The pertinent questions which the paper seeks to answer amongst others are: What are the requirements of a valid award? What are the procedures for making recourse against an arbitral award? And what are the grounds for making recourse against arbitral award? Taking into cognisance that the essence of successful recourse against arbitral award is to set it aside, this paper addresses the above questions and concludes with recommendation among others that parties and their legal representatives should ensure that both parties and arbitral tribunal comply with the provisions of the law regulating the agreement of parties and arbitral proceedings to avoid recourse against arbitral award.